Children’s participation in the development, use and evaluation of support interventions for children of a parent diagnosed with cancer: a scoping review protocol - Anne Wennick; Maria Samuelsson; Kristofer Hansson; Marie-Louise Möllerberg; Kristina Edman; Karin Enskär (BMJ Open)
Introduction At times of parental cancer, children’s health and well-being are at risk, which is why interventions to support these children have been developed. When developing such interventions, engagement of the population under study in research is endorsed to enhance relevance of research questions and to enhance uptake and dissemination of the findings. Since no previous review has mapped the ways children participate in the development, use and evaluation of these support interventions, the focus of the upcoming scoping review is to identify gaps in the literature for guidance of future research.Methods and analysis The scoping review is guided by the methodological framework developed by Arksey and O’Malley. A preliminary search strategy was performed in PubMed in November 2020, refined in March 2021 and applied in PubMed, PsycINFO and CINAHL. Additional searches were performed in Google Scholar and SwePub, and reference lists were hand searched. Refined searches will be conducted in February 2024. The multidisciplinary research team will independently screen titles, abstracts and full-text articles for relevance. Then, relevant studies will be critically evaluated using the Joanna Briggs Critical Appraisal Skills Tools. Data will be extracted using an extraction form and analysed deductively. A descriptive summary of study characteristics and the research process will be presented, including a flow chart. The reporting of the study will be guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews Checklist.Ethics and dissemination Being a secondary analysis, ethical approval is not needed. Still, relevant studies will be reviewed for ethical approval as a criterion for inclusion. The findings will be used to inform future studies and will be published in a scientific journal as well as presented at conferences and organisations for children’s rights.